A influência da irmandade muçulmana do Egito na política externa do governo Morsi: do engajamento político-social à chegada ao poder (2011-2013). - Bellinati, Gisele (2016)
The current work has the aim to study the Egypt’s Muslim Brotherhood group actions in the process of elaboration of the country’s foreign policy, at the time Mohamed Morsi takes over the government of Egypt, in the year 2011. The group has an extensive political activism historic in the country, and in the past decades has shown how its significance has grown in the political scenario. With the Revolution which overthrew the dictator Mubarak from the power in 2011, the Muslim Brotherhood had the opportunity to stand out and extend their Islamic ideals inside the society. Thus, this piece of work suggest the comprehension of the Muslim Brotherhood activities in Egypt, and how these actions culminated in changes of the Foreign Policy spread through Morsi during his mandate. In order to do this, we will analyze how ideas and ideologies from groups can manipulate in the procedure of Foreign Policy, so we can illustrate the role of the Muslim Brotherhood in the process, and how their ideals were relevant to the shape and development in one of the major religious groups nowadays.